Asplenium contiguum Kaulf. (Aspleniaceae), a new record for Thailand - Lindsay, Stuart; Middleton, David J.; Suddee, Somran (Thai Forest Bulletin (Botany), 2014)
Asplenium contiguum Kaulf., a new record for Thailand, is described and illustrated.